2013
DOI: 10.7324/japs.2013.30207
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity of phenolic and flavonoid fractions of Cleome gynandra and Maerua angolensis of Burkina Faso

Abstract: Cleome gynandra L. and Maerua angolensis DC (Forsk) are two species of Capparidaceae family and of which the traditional uses are directed much against the inflammatory diseases, cancer and cellular ageing. The aim of this study is to measure the anti-FRAP, anti-ABTS and anti-DPPH activities through the n-hexane (n-H), dichloromethanolic (DCM), acetonitrile (ACN), ethyl acetate (EA), methanolic (MeOH) and n-butanol (n-BuOH) fractions of each species. We thus quantified the total phenolic and total flavonoids i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 26 publications
0
9
1
Order By: Relevance
“…In addition, phenolic compounds are reported to play essential roles in defense mechanisms against pathogens, parasites, and predators of plants, suggesting that the accessions that have a high content of phenolic compounds could be possible sources of genes for insect pests resistance. In this study, the mean of TPC of the spider plant accessions (123.3 mg GAE/g) was higher than the values reported by Jiménez-Aguilar and Grusak (2017), but lower than the findings of Meda et al (2013), who reported 133.0 mg GAE/g. In addition, other authors found lower levels of TPC (Somers et al, 2020), which were comparable to some African vegetables (Jiménez-Aguilar and Grusak, 2015).…”
Section: Discussion Phytochemical Content In Different Accessions Of Spider Plantcontrasting
confidence: 85%
See 1 more Smart Citation
“…In addition, phenolic compounds are reported to play essential roles in defense mechanisms against pathogens, parasites, and predators of plants, suggesting that the accessions that have a high content of phenolic compounds could be possible sources of genes for insect pests resistance. In this study, the mean of TPC of the spider plant accessions (123.3 mg GAE/g) was higher than the values reported by Jiménez-Aguilar and Grusak (2017), but lower than the findings of Meda et al (2013), who reported 133.0 mg GAE/g. In addition, other authors found lower levels of TPC (Somers et al, 2020), which were comparable to some African vegetables (Jiménez-Aguilar and Grusak, 2015).…”
Section: Discussion Phytochemical Content In Different Accessions Of Spider Plantcontrasting
confidence: 85%
“…These antioxidants neutralize/scavenge free oxygen and nitrogen radicals and prevent many diseases in the human body (Sarker and Oba, 2018e). Dietary phytochemicals of leafy vegetables, i.e., phenolics, are versatile compounds, such as phenol, coumarins, different groups of phenolic acids, and different groups of flavonoids, including flavonols, flavones, flavanols, flavanones, anthocyanins, chalcones, and different groups of non-flavonoids, including tannins, lignans and stilbenes that have been reported to have important antioxidant properties (Meda et al, 2013;Sarker and Oba, 2020e,f). The phytochemicals are distributed widely and occur in different concentrations within and across plant species.…”
Section: Discussion Phytochemical Content In Different Accessions Of Spider Plantmentioning
confidence: 99%
“…The antioxidant power was carried out using the DPPH method according to the spectrophotometric method described by Meda et al, (2013). 20 In a test tube containing 0.375 ml of the sample (0.1 mg/ml) of each extract, 0.75 ml of the DPPH solution (20 mg /l) was introduced.…”
Section: Dpph Radical Methodsmentioning
confidence: 99%
“…The antioxidant power was carried out using the DPPH method according to the spectrophotometric method described by Meda et al, (2013). 20 In a test tube containing 0.375 ml of the sample (0.1 mg/ml) of each extract, 0.75 ml of the DPPH solution (20 mg /l) was introduced. After 15 minutes' post-incubation of the mixture at room temperature in the dark, the absorbances were immediately read at 517 nm with a spectrophotometer (GENESYS 30).…”
Section: Dpph Radical Methodsmentioning
confidence: 99%
“…The nutritional composition of Cleome gynandra L. (Cleomaceae) makes this crop an added value to be taken into account in achieving food and nutritional security for consumers (Meda et al, 2013;Chand et al, *Corresponding author. E-mail: cheickboureimasakande@gmail.com.…”
Section: Introductionmentioning
confidence: 99%